PEMAHAMAN KONSEP MACROERGONOMICS DALAM UPAYA PENCEGAHAN KECELAKAAN KERJA BIDANG KONSTRUKSI: SEBUAH ANALISA DESKRIPTIF PENDEKATAN MODEL PEMIKIRAN MAKRO, MESO DAN MIKRO - Samiranto, Edi; Samiranto, Erna; Sulistyadi, Kohar (JURNAL GAUNG INFORMATIKA, 2015)
In Indonesia the safety program in construction projects has not been a concern of all parties because Indonesia is still listed as the country with the highest level ofaccidents. The number of accidents in Indonesia is also the highest in the ASEAN region. There are almost 32% of accident cases that occur in the construction sector involving all types of construction projects such as the construction of roads, bridges, tunnels, dams and other constructions. One of the hazards of a construction activity is ergonomic hazards, so that from the phenomenon of ergonomic hazards that dominate and even escalate into workplace accidents in the construction sector, it is important to explore the role of ergonomics in preventing work accidents in the construction sector. At the Micro level, an important aspect that is the focus of this paper is the Implementation of Construction Works in the context of Macroergonomics in developing and implementing an Ergonomic Construction Management System. This Management System focuses on the focus of macroergonomics, namely aspects of Human, Technology, Organization and the Environment of the Company.  acroergonomic which covers organizational ergonomics and social ergonomics is the development of microergonomies that need attention in construction activities in Indonesia. Because of the still high number of construction work accidents, the government's efforts are to issue Construction SMK3 and other regulatory packages related to construction work safety. The Owner of the Construction Project must actively monitor and evaluate the implementation of the construction work not only on the dimensions of physical work and fulfillment of the technical requirements of the building but need to proactively monitor and evaluate safety performance, especially in the ergonomics field